![SearchIcon](https://vmkt.vedantu.com/vmkt/PROD/png/bdcdbbd8-08a7-4688-98e6-4aa54e5e0800-1733305962725-4102606384256179.png)
If \[\dfrac{{\tan 3\theta }}{{\tan \theta }} = 4\] , then \[\dfrac{{\sin 3\theta }}{{\sin \theta }}\] equals:
(A) \[\dfrac{8}{3}\]
(B) \[\dfrac{4}{5}\]
(C) \[\dfrac{3}{4}\]
(D) None of these
Answer
459.6k+ views
Hint:
According to the question, use the formula \[\tan 3\theta = \dfrac{{3\tan \theta - {{\tan }^3}\theta }}{{1 - 3{{\tan }^2}\theta }}\] and simplify to get the value of \[\tan \theta \] and calculate the value in terms of sin to find the required answer. Then again use the formula of \[\sin 3\theta = 3\sin \theta - 4{\sin ^3}\theta \] to find the value of \[\dfrac{{\sin 3\theta }}{{\sin \theta }}\].
Formula used:
Here, we use the trigonometric formulas that is \[\tan 3\theta = \dfrac{{3\tan \theta - {{\tan }^3}\theta }}{{1 - 3{{\tan }^2}\theta }}\] and \[\sin 3\theta = 3\sin \theta - 4{\sin ^3}\theta \].
Complete step by step solution:
As it is given, \[\dfrac{{\tan 3\theta }}{{\tan \theta }} = 4\]
Take \[\tan \theta \] on the right hand side in multiply.
So we get, \[\tan 3\theta = 4\tan \theta \]
Here, we will use the formula of \[\tan 3\theta = \dfrac{{3\tan \theta - {{\tan }^3}\theta }}{{1 - 3{{\tan }^2}\theta }}\]
On substituting we get,
\[\dfrac{{3\tan \theta - {{\tan }^3}\theta }}{{1 - 3{{\tan }^2}\theta }} = 4\tan \theta \]
Taking \[\tan \theta \] common in numerator from right hand side,
\[\dfrac{{\tan \theta \left( {3 - {{\tan }^2}\theta } \right)}}{{1 - 3{{\tan }^2}\theta }} = 4\tan \theta \]
Cancelling \[\tan \theta \] from both right hand side and left hand side,
So we get,
\[\dfrac{{3 - {{\tan }^2}\theta }}{{1 - 3{{\tan }^2}\theta }} = 4\]
Taking denominator of left hand side to the right hand side,
\[3 - {\tan ^2}\theta = 4(1 - 3{\tan ^2}\theta )\]
\[3 - {\tan ^2}\theta = 4 - 12{\tan ^2}\theta \]
After simplifying we get,
\[ - {\tan ^2}\theta + 12{\tan ^2}\theta = 4 - 3\]
\[11{\tan ^2}\theta = 1\]
So, \[{\tan ^2}\theta = \dfrac{1}{{11}}\]
After taking square root on both side we get,
\[\tan \theta = \sqrt {\dfrac{1}{{11}}} \]
As we know \[\sqrt 1 = 1\] and \[\sqrt {11} = \sqrt {11} \]
Substituting all the calculated values we get,
\[\tan \theta = \dfrac{1}{{\sqrt {11} }}\]
As we know \[\tan \theta = \dfrac{{Perpendicular}}{{Base}}\]
So, we will draw a right angled triangle \[\Delta ABC\] having angle \[\theta \] , base \[ = \sqrt {11} \] and perpendicular = 1 as shown in figure.
As of now we will calculate Hypotenuse by using the Pythagoras theorem that is \[{H^2} = {P^2} + {B^2}\]
So, we will substitute all the values of P and B to get the value of H .
In right angled triangle \[\Delta ABC\]
\[{H^2} = {1^2} + {\left( {\sqrt {11} } \right)^2}\]
After calculating squares we get,
\[{H^2} = 1 + 11\]
\[{H^2} = 12\]
After taking square root on both side we get,
\[H = \sqrt {12} = 2\sqrt 3 \]
So, now we will calculate \[\sin \theta = \dfrac{P}{H}\]
Putting P = 1 and \[H = 2\sqrt 3 \] we get,
\[\sin \theta = \dfrac{1}{{2\sqrt 3 }}\]
As, according to the question we have to calculate \[\dfrac{{\sin 3\theta }}{{\sin \theta }}\]
Here, we use the formula of \[\sin 3\theta = 3\sin \theta - 4{\sin ^3}\theta \]
After substituting we get,
\[ \Rightarrow \dfrac{{3\sin \theta - 4{{\sin }^3}\theta }}{{\sin \theta }}\]
Taking \[\sin \theta \] common from numerator and cancelling \[\sin \theta \] from numerator and denominator we get,
\[ \Rightarrow 3 - 4{\sin ^2}\theta \]
Putting the value of \[\sin \theta = \dfrac{1}{{2\sqrt 3 }}\] in the above equation.
\[ \Rightarrow 3 - 4{\left( {\dfrac{1}{{2\sqrt 3 }}} \right)^2}\]
On simplifying we get,
\[ \Rightarrow 3 - \dfrac{1}{3}\]
By taking L.C.M we get,
\[ \Rightarrow \dfrac{8}{3}\]
So, option (A) \[\dfrac{8}{3}\] is correct.
Note:
To solve these types of questions, you must remember the trigonometric formulas and conversion of trigonometric values. For conversion you can simply use Pythagoras theorem to find the required value.
According to the question, use the formula \[\tan 3\theta = \dfrac{{3\tan \theta - {{\tan }^3}\theta }}{{1 - 3{{\tan }^2}\theta }}\] and simplify to get the value of \[\tan \theta \] and calculate the value in terms of sin to find the required answer. Then again use the formula of \[\sin 3\theta = 3\sin \theta - 4{\sin ^3}\theta \] to find the value of \[\dfrac{{\sin 3\theta }}{{\sin \theta }}\].
Formula used:
Here, we use the trigonometric formulas that is \[\tan 3\theta = \dfrac{{3\tan \theta - {{\tan }^3}\theta }}{{1 - 3{{\tan }^2}\theta }}\] and \[\sin 3\theta = 3\sin \theta - 4{\sin ^3}\theta \].
Complete step by step solution:
As it is given, \[\dfrac{{\tan 3\theta }}{{\tan \theta }} = 4\]
Take \[\tan \theta \] on the right hand side in multiply.
So we get, \[\tan 3\theta = 4\tan \theta \]
Here, we will use the formula of \[\tan 3\theta = \dfrac{{3\tan \theta - {{\tan }^3}\theta }}{{1 - 3{{\tan }^2}\theta }}\]
On substituting we get,
\[\dfrac{{3\tan \theta - {{\tan }^3}\theta }}{{1 - 3{{\tan }^2}\theta }} = 4\tan \theta \]
Taking \[\tan \theta \] common in numerator from right hand side,
\[\dfrac{{\tan \theta \left( {3 - {{\tan }^2}\theta } \right)}}{{1 - 3{{\tan }^2}\theta }} = 4\tan \theta \]
Cancelling \[\tan \theta \] from both right hand side and left hand side,
So we get,
\[\dfrac{{3 - {{\tan }^2}\theta }}{{1 - 3{{\tan }^2}\theta }} = 4\]
Taking denominator of left hand side to the right hand side,
\[3 - {\tan ^2}\theta = 4(1 - 3{\tan ^2}\theta )\]
\[3 - {\tan ^2}\theta = 4 - 12{\tan ^2}\theta \]
After simplifying we get,
\[ - {\tan ^2}\theta + 12{\tan ^2}\theta = 4 - 3\]
\[11{\tan ^2}\theta = 1\]
So, \[{\tan ^2}\theta = \dfrac{1}{{11}}\]
After taking square root on both side we get,
\[\tan \theta = \sqrt {\dfrac{1}{{11}}} \]
As we know \[\sqrt 1 = 1\] and \[\sqrt {11} = \sqrt {11} \]
Substituting all the calculated values we get,
\[\tan \theta = \dfrac{1}{{\sqrt {11} }}\]
As we know \[\tan \theta = \dfrac{{Perpendicular}}{{Base}}\]
So, we will draw a right angled triangle \[\Delta ABC\] having angle \[\theta \] , base \[ = \sqrt {11} \] and perpendicular = 1 as shown in figure.
![seo images](https://www.vedantu.com/question-sets/5c5f047c-2798-4b5f-b0dc-7618e8d5eef2480237512303399058.png)
As of now we will calculate Hypotenuse by using the Pythagoras theorem that is \[{H^2} = {P^2} + {B^2}\]
So, we will substitute all the values of P and B to get the value of H .
In right angled triangle \[\Delta ABC\]
\[{H^2} = {1^2} + {\left( {\sqrt {11} } \right)^2}\]
After calculating squares we get,
\[{H^2} = 1 + 11\]
\[{H^2} = 12\]
After taking square root on both side we get,
\[H = \sqrt {12} = 2\sqrt 3 \]
So, now we will calculate \[\sin \theta = \dfrac{P}{H}\]
Putting P = 1 and \[H = 2\sqrt 3 \] we get,
\[\sin \theta = \dfrac{1}{{2\sqrt 3 }}\]
As, according to the question we have to calculate \[\dfrac{{\sin 3\theta }}{{\sin \theta }}\]
Here, we use the formula of \[\sin 3\theta = 3\sin \theta - 4{\sin ^3}\theta \]
After substituting we get,
\[ \Rightarrow \dfrac{{3\sin \theta - 4{{\sin }^3}\theta }}{{\sin \theta }}\]
Taking \[\sin \theta \] common from numerator and cancelling \[\sin \theta \] from numerator and denominator we get,
\[ \Rightarrow 3 - 4{\sin ^2}\theta \]
Putting the value of \[\sin \theta = \dfrac{1}{{2\sqrt 3 }}\] in the above equation.
\[ \Rightarrow 3 - 4{\left( {\dfrac{1}{{2\sqrt 3 }}} \right)^2}\]
On simplifying we get,
\[ \Rightarrow 3 - \dfrac{1}{3}\]
By taking L.C.M we get,
\[ \Rightarrow \dfrac{8}{3}\]
So, option (A) \[\dfrac{8}{3}\] is correct.
Note:
To solve these types of questions, you must remember the trigonometric formulas and conversion of trigonometric values. For conversion you can simply use Pythagoras theorem to find the required value.
Recently Updated Pages
Master Class 11 Economics: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 11 Business Studies: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 11 Accountancy: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The correct geometry and hybridization for XeF4 are class 11 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Water softening by Clarks process uses ACalcium bicarbonate class 11 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
With reference to graphite and diamond which of the class 11 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Trending doubts
10 examples of friction in our daily life
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Difference Between Prokaryotic Cells and Eukaryotic Cells
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
State and prove Bernoullis theorem class 11 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What organs are located on the left side of your body class 11 biology CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
How many valence electrons does nitrogen have class 11 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)